2010
DOI: 10.1016/j.snb.2010.05.054
|View full text |Cite
|
Sign up to set email alerts
|

Micro gas preconcentrator in porous silicon filled with a carbon absorbent

Abstract: International audienceThis paper presents the development of a gas preconcentrator based on a micro-channel in porous silicon filled with carbon nanopowders by a micro-fluidic process. The particularity of this device is its applicability in the fields of atmospheric pollution monitoring by targeting VOCS (volatiles organic compounds). Various designs of micro-devices have been investigated and a special focus has been dedicated to the carbon adsorbent. The optimization of the device and its operation were dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 18 publications
0
38
0
3
Order By: Relevance
“…The different channels are designed with the necessity of having some pillars or walls within the channels in order to control the powders deposition by fluidic solutions [23,24] . The neutral microchannel is designed without structures in the internal chamber while the zigzag design with channel system at inlet/outlet, mostly used in this work, is made with "V" shaped structures in order to improve the flow distribution not only during the adsorbent deposition but also during experiments.…”
Section: Preconcentratormentioning
confidence: 99%
See 3 more Smart Citations
“…The different channels are designed with the necessity of having some pillars or walls within the channels in order to control the powders deposition by fluidic solutions [23,24] . The neutral microchannel is designed without structures in the internal chamber while the zigzag design with channel system at inlet/outlet, mostly used in this work, is made with "V" shaped structures in order to improve the flow distribution not only during the adsorbent deposition but also during experiments.…”
Section: Preconcentratormentioning
confidence: 99%
“…It was observed that the use of porous silicon has increased the quantity of deposited carbon in the micro-channels. In fact, the presence of pores on the surface of the walls constitutes an important asset to get a good binding layer and thus to increase the quantity of adsorbent filled in the micro-channel compared to non-porous silicon [23] .…”
Section: Adsorbent Depositionmentioning
confidence: 99%
See 2 more Smart Citations
“…They have been successfully employed for a variety of applications spanning from explosives detection [6] to environmental monitoring [7] and more recently in medical diagnostics of chronic obstructive pulmonary diseases [8]. Additionally, the combination of GC/IMS or GC/DMS with a preconcentrator is increasingly becoming common use due to its performance improvement both in terms of selectivity and sensitivity [9,10].…”
Section: Introductionmentioning
confidence: 99%